A Study of Sexual Relationship Power among Young Women Who Inject Drugs and Their Sexual Partners. (3rd July 2018) - Morris, Meghan D.; Montgomery, Martha E.; Briceno, Alya; Evans, Jennifer L.; Andrew, Erin V. W.; Page, Kimberly; Hahn, Judith A.
ABSTRACT: Background : To date, research applying the Sexual Relationship Power Scale (SRPS) has been limited to sexual risk behaviors. Objective : We measured levels of sexual relationship power and examined associations between sexual relationship power and injecting and sexual behaviors that place women at increased risk for blood borne infections. Methods : Using data from a cross-sectional study of young women who inject drugs (WWID) in San Francisco, USA, logistic regression analysis identified independent associations between SRPS and subscale scores (relationship control [RC] and decision making dominance [DMD]) and injecting and sexual behaviors. Results : Of the 68 young WWID, 24 (34%) reported receptive syringe sharing, 38 (56%) reused/shared a cooker to prepare drugs, and 25 (37%) injected someone else's drug residue during the three-months prior to enrollment. Most (60, 88%) reported condomless sex with main sex-partner, 8 (12%) reported transactional sex, and 36 (53%) had two or more recent sex partners. The median SRPS score was 2.98 (IQR: 2.65, 3.18), 3.23 (IQR: 3.23, 3.57) for RC and 2.40 (IQR: 2.20, 2.60) for DMD. No significant associations were detected between SRPS or DMD and injecting or sexual risk behaviors. After adjusting for gender and years injecting, for every one-point increase in RC, women had a 6.70 lower odds of recent condomless sex (95%CI: 0.92, 50.00, p = 0.06), and a 3.90 lower odds of recent transactional sex (95%CI: 1.22, 12.50, p = 0.02). Conclusion : Our study findings suggest that some components of sexual relationship power may play a role in sexual risk, but not in injecting risk.